Design description and validation results for the IFMIF High Flux Test Module as outcome of the EVEDA phase. (December 2016) - Arbeiter, F.; Abou-Sena, A.; Averhals, J.; Böttcher, T.; Chen, Y.; Dolensky, B.; Fischer, U.; Heinzel, A.; Heinzel, V.; Heupel, T.; Jacquet, P.; Klein, Ch.; et al.
Highlights: A device for irradiation of SSTT specimens in IFMIF has been designed. The design process encompasses neutronic, thermal-hydraulic and mechanical analyses. Prototypes have been successfully built and tested. Abstract: During the Engineering Validation and Engineering Design Activities (EVEDA) phase (2007-2014) of the International Fusion Materials Irradiation Facility (IFMIF), an advanced engineering design of the High Flux Test Module (HFTM) has been developed with the objective to facilitate the controlled irradiation of steel samples in the high flux area directly behind the IFMIF neutron source. The development process addressed included manufacturing techniques, CAD, neutronic, thermal-hydraulic and mechanical analyses complemented by a series of validation activities. Validation included manufacturing of 1:1 parts and mockups, test of prototypes in the FLEX and HELOKA-LP helium loops of KIT for verification of the thermal and mechanical properties, and irradiation of specimen filled capsule prototypes in the BR2 test reactor. The prototyping activities were backed by several R&D studies addressing focused issues like handling of liquid NaK (as filling medium) and insertion of Small Specimen Test Technique (SSTT) specimens into the irradiation capsules. This paper provides an up-todate design description of the HFTM irradiation device, and reports on the achieved performance criteria related to the requirements. Results of the validation activities are accounted for and the most important issues for further development are identified.